2003
DOI: 10.1536/jhj.44.403
|View full text |Cite
|
Sign up to set email alerts
|

Value of Measuring Myocardial Performance Index by Tissue Doppler Echocardiography in Normal and Diseased Heart

Abstract: SUMMARYMyocardial performance index (MPI) is a simple and reproducible method for the assessment of overall cardiac function. In this study, we evaluated the applicability and usefulness of pulsed-wave tissue Doppler echocardiography (TDE) as a tool to calculate MPI in comparision with a conventional Doppler method.Twenty-five patients with previous myocardial infarction (MI) and 15 healthy subjects were included. In order to calculate MPI by TDE, isovolumetric contraction time (IVCT), isovolumetric relaxation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
26
1
2

Year Published

2006
2006
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(34 citation statements)
references
References 11 publications
(8 reference statements)
5
26
1
2
Order By: Relevance
“…It is reported that the normal value of TDI Tei index range from 0.29-0.36. 11,16,18 The present study illustrates that TDI Tei index is higher in hypertensives, and more prominent in LVH group, but E/A shows no difference between NLVH and LVH groups, which suggests that TDI Tei index is a sensitive parameter for evaluation of global ventricular function before developing ventricular hypertrophy. The present study also supports the opinion that systolic dysfunction coexists with diastolic dysfunction in hypertensives.…”
Section: Discussionmentioning
confidence: 47%
See 2 more Smart Citations
“…It is reported that the normal value of TDI Tei index range from 0.29-0.36. 11,16,18 The present study illustrates that TDI Tei index is higher in hypertensives, and more prominent in LVH group, but E/A shows no difference between NLVH and LVH groups, which suggests that TDI Tei index is a sensitive parameter for evaluation of global ventricular function before developing ventricular hypertrophy. The present study also supports the opinion that systolic dysfunction coexists with diastolic dysfunction in hypertensives.…”
Section: Discussionmentioning
confidence: 47%
“…Tei index was reported to be simple, reproducible and independent of HR and blood pressure. 25 Tissue Doppler imaging Tei index was used to evaluate LV function in patients with dilate cardiomyopathy, 16 myocardial infarction 18 and hypertension. 11 In those disease states, Tei index was found to be higher than in normal subjects, and TDI Tei index correlated well with traditional Tei index.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…4,5 Tissue Doppler imaging (TDI) is an alternative noninvasive approach to obtain the cardiac time intervals and thereby the MPI. 6,7 With this method, the time intervals can be obtained from 1 projection and 1 cardiac cycle. In contrast, with the conventional method described by Tei et al, 5 the time intervals are obtained from 2 projections and at least 2 cardiac cycles 4,5 and may therefore be prone to errors caused by heart rate variability, which is not a concern with TDI.…”
mentioning
confidence: 99%
“…Therefore, regional wall motion disorders develop in the early phase of the disease, although general cardiac function is normal (4). Newly developed tissue Doppler imaging intended to demonstrate cardiac dysfunction in the early phase has started to be used in various patients groups and has been shown to be superior to conventional echocardiographic methods (5)(6)(7)(8)(9).…”
Section: Introductionmentioning
confidence: 99%